Effect of phototherapy on peroxidase, myeloperoxidase activities, oxidized protein and calcium levels in Iraqi vitiligo patients - Naama, Noor Abdulhussain; Zainulabdeen, Jwan Abdulmohsin (Journal of Neonatal Surgery, 2025)
Background: Vitiligo is a skin condition in which the skin loses its color due to the destruction of pigment cells , meantime oxidative stress plays a significant role in triggering this damage. Peroxidases are members of the oxidoreductases enzymes that reduce hydroperoxides via the decomposition of a great variety of substrates into harmlessly components. The oxidative cycle of peroxidases involves the reduction of an electron-donor substrate, in the presence of hydrogen peroxide . The heme enzyme; Myeloperoxidase (MPO) is released in the europhilic granules of neutrophils, and to a lesser degree in the lysosomes of monocytes to forming reactive oxygen intermediates (hypochlorous acid ; a powerful oxidant) to kill internalized bacteria and other pathogens. Objective: The study aims to assess oxidative stress in vitiligo patients by measuring peroxidase and myeloperoxidase activities to explore their role in the diseases and the effect of phototherapy on the oxidative stress status represented by the oxidized proteins , enzymes activities and the level of calcium. Materials and methods: One hundred fifty participants were included in the present study divided equally to three groups as follow: patients treated with NB-UVB(PUV), newly diagnosis groups(PV) , and apparently healthy as control(C). All studied parameters were determined by using appropriate spectrophotometric method. Results: Results showed high significant increases in the serum oxidized proteins level , as well peroxidases and MPO activities in both patients groups (PUV and PN) in comparison to that of C group While, no significant was observed in PUV compared with PN group for oxidized proteins level and significant increase in PN over PUV in activities of the two enzymes. In contrast the results appeared a significant decrease in calcium level of PUV when compared with C. whilst, no significant changes were seen between the PN and C group as well as PUV with PN. Conclusion: The study showed that phototherapy reduces oxidative stress in vitiligo patients, reflected in decreased activity of antioxidant enzymes, resulting from reduced defense needs. Changes in oxidized protein and calcium were also observed, indicating a clear effect of the treatment on internal balance.